2010
DOI: 10.1590/s0073-47212010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Morcegos da região sul do Brasil: análise comparativa da riqueza de espécies, novos registros e atualizações nomenclaturais (Mammalia, Chiroptera)

Abstract: ABSTRACT. Bats from southern Brazil: comparative analysis of species richness, new records and nomenclatural update (Mammalia, Chiroptera). A comparative analysis of the patterns of bat species richness in southern Brazil is presented, as well as similarity analyses among states. The highest richness of bat species is found in the state of Paraná, with 64 species, followed by Santa Catarina with 46, and Rio Grande do Sul, with 40. The family Phyllostomidae plays an important role in determining this pattern. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
1
30
0
3
Order By: Relevance
“…Therefore, our combined evidence supports the existence of two distinct taxa, given that they are: 1) sympatric; 2) morphologically distinct (in fur coloration); 3) morphometrically different; and 4) morphometrically different from one another to an extent that is similar to or greater than the differences among other species in their evolutionary group. Therefore, we agree with BARQUEZ (2006), PASSOS et al (2010), BARQUEZ et al (2011), andPAGLIA et al (2012) and consider M. levis and M. dinellii to be separate species.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our combined evidence supports the existence of two distinct taxa, given that they are: 1) sympatric; 2) morphologically distinct (in fur coloration); 3) morphometrically different; and 4) morphometrically different from one another to an extent that is similar to or greater than the differences among other species in their evolutionary group. Therefore, we agree with BARQUEZ (2006), PASSOS et al (2010), BARQUEZ et al (2011), andPAGLIA et al (2012) and consider M. levis and M. dinellii to be separate species.…”
Section: Discussionsupporting
confidence: 91%
“…Gregorin et al (2006) and stated that this form, distinguished from the nominal Thyroptera t. tricolor by a more yellowish venter and a smaller forearm, may represent a distinct species. Esbérard et al (2007) found five additional records of T. tricolor for the Atlantic Forest that matched the description of T. t. juquiaensis and Passos et al (2010) published the southernmost known record of the species, for the Brazilian state of Paraná, south of São Paulo.…”
Section: Family Thyropteridae Miller 1907mentioning
confidence: 71%
“…The specimen MZUSP 2020 is badly damaged and has no associated skull, but its identification could be made based on the absence of a dorsal white stripe, presence of facial stripes and relatively small forearm. Passos et al (2010) reported the southernmost record of the species, for the E state of Paraná. ); Guarulhos, area owned by a beverage company ; Guarulhos, area with poultry pen, surrounded by forest ; Guarulhos, Candinhas House ; Guarulhos, Horto Florestal ; Guarulhos, private property on a hill ; Guarulhos, private property used as recreational area ; Guarulhos, rural area …”
Section: Subfamily Stenodermatinae Gervais 1856mentioning
confidence: 99%
“…The primary reference for the occurrence of the species in Brazil is, therefore, LaVal (1973a). 42 Although recorded for Brazil since 2010 (Passos et al 2010), only recently Myotis dinellii was formally raised to the species level, distinct from Myotis levis (Miranda et al 2013). 43 Myotis guaycuru was recently confirmed as a junior synonym of Myotis simus by Moratelli et al (2011b); therefore, the original description of M.…”
Section: As a Subspecies Of Dermanura Glauca (Referred As Artibeus Glmentioning
confidence: 99%